ANALISIS PERBANDINGAN NILAI SHADOW FADING PADA MODEL PROPAGASI STANFORD UNIVERSITY INTERIM (SUI) DENGAN METODE SIMULASI DAN DRIVE TEST - Bintang Cahyadi, M; Sudiarta, P K; Diafari Djuni Hartawan, I G A K (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p26, 2021)
Stanford University Interim (SUI) is a propagation model developed by the institute of Electrical and Electronic Engineers (IEEE). SUI propagation is divided into three conditions, namely conditions A, B and C. Of the three conditions, there is a correction factor (shadow fading) caused by buildings and trees whose values are 8.2 - 10.6 dB. This research will analyze the comparison of the shadow fading value in the SUI propagation model. The method used is a simulation using radio atoll planning and drive test measurements on the BTS LTE_Kampus_Udayana, LTE_Jimbaran and LTE_GapuraUdayanaRoad in the Bukit Jimbaran area. The results of the drive test will be compared with the simulation in Conditions A, B and C and look for the shadow fading value. The results obtained are for BTS LTE_Kampus_Udayana, LTE_Jimbaran and LTE_GapuraUdayanaRoad closer to condition A with an average difference of -6.45 dBm, this is supported by the conditions in the three BTS settings where the contours are hilly and the intensity of the trees and the buildings are high to moderate. As for the shadow fading value, the simulation results were obtained at 8.31 dB and the drive test was 11.47 dB.